Pengaruh ekstrak daun durian (Durio zibethinusmurr) terhadap kematian larva nyamuk aedes aegypti - Fajriansyah Fajriansyah; Ferdi Riansyah; Sastri Sastri (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: The Aedes aegypti mosquito is the main vector for dengue fever. Larvicidal eradication is a vector control program worldwide. The most commonly used larvicide is abated. Durian leaves contain saponins, flavonoids, and steroids where saponins will interfere with the lipoid layer and disrupt the endocuticular protein layer so that toxic compounds easily enter the body of the larvae.Objectives: This study aims to determine the effect of durian leaf extract on the death of Aedes aegypti larvae.Methods: Using 240 Aedes aegypti larvae with three treatments and three repetitions, observations of the number of dead larvae were carried out every 90 minutes for 5 hours, and data were analyzed using a one-way ANOVA test and LSD test.Results: The results showed that the average number of dead mosquito larvae at a concentration of 10 ml/100 ml (12 larvae); a concentration of 20 ml/100 ml (15 dead larvae); and a concentration of 30 ml/100 ml (18 dead larvae); The results of the ANOVA test showed that there was an effect of giving durian leaf extract on the death of Aedes aegypti larvae with a value of p = 0.004. The LSD test results showed that there was a significant difference in the number of dead mosquito larvae between concentrations of 30 ml, 20 ml, and 10 ml.Conclusion: It can be concluded that durian leaf extract can kill Aedes aegypti mosquito larvae, so it can be used as an alternative larvicide.